PENGUKURAN ENVIRONMENTAL AUDIT DALAM KONTEKS INDONESIA - Inova Fitri Siregar; Rinayanti Rasyad; Dini Onasis (Komunitas Manajemen Kompetitif, 2026)
The purpose of this study is to determine the criteria that can be used to measure environmental audits from the perspective of greenhouse gas emission reduction, as interpreted in sustainability reporting. This study also examines how environmental audit measurement can be developed, including the application of an empirical research model to establish standards based on investor needs, which will be created to maximize stakeholder needs.The method used in this study is a scientific approach or Grounded Theory. A review of the theories discussed indicates that no similar research exists. In this study, Grounded Theory is applied in several stages. Basic concepts related to environmental audit indicators are obtained from a combination of previous literature, the GHG Protocol, and the Validation and Verification Standard for Funding for Risk Mitigation Actions (DRAM), and are then reinforced with interview data.The results of the study indicate that, although developing new environmental audit procedures is challenging, it is achievable. To overcome this difficulty, this study creates a draft audit procedure based on project results, intended to be easily adapted for practical application. To achieve successful GHG emission reduction, i.e. every organization practices environmental audits and every company is required to calculate GHG emissions as a legal requirement, GHG emission reporting and risk mitigation should not be expensive, time-consuming, or resource-intensive to prepare.